Assessment of ecological sustainability of the landscape of the Prypiat River basin within the Volyn region - Boіaryn, Mariia V.; Biedunkova, Olha O.; Netrobchuk, Iryna M.; Radzii, Volodymyr F.; Voloshyn, Volodymyr U. (My University, 2023)
The relevance of the research lies in the fact that, in the context of the global concept of sustainable development, one of the leading tasks is to maintain the sustainability of natural ecosystems by finding optimal strategies for the development of socio-economic systems. The purpose of the research is to assess the environmental sustainability of the landscapes of the Prypiat River basin within the territorial communities of the Volyn Oblast in the current conditions of the region’s development. The methods used to achieve this goal included the calculation of the landscapeecological sustainability coefficient based on the systematization of statistical reporting data, followed by comparative geographical analysis and environmental mapping using ArcMap and ArcGIS Pro. The main results of the research show that the coefficient of ecological stability of landscapes in the Prypiat River basin is in the range of 0.22-5.39 and assesses landscapes from the level of “unstable with pronounced instability” to “stable, with pronounced stability”. The distribution of land areas in the territorial communities located in the Tsyr sub-basin determines the landscape characterization at the level of “stable, with pronounced stability”. Within the territorial communities of the Vyzhivka sub-basin and the upper reaches of the Prypiat River, the landscapes are “conditionally stable” – “stable”. Within the communities of the Turia sub-basin – from “unstable” to “stable, with pronounced stability”. Within the communities of the Stokhid sub-basin – from “unstable” to “stable, with pronounced stability”. The territorial communities of the middle part of the Styr sub-basin are represented by landscapes ranging from “unstable, with pronounced instability” to “stable, with pronounced stability”. In general, more ecologically stable landscapes are located in the northern part of Volyn Oblast, due to the large areas of forested land. Environmental instability of landscapes is typical for the southern part of the region due to large areas of ploughed land. The practical value of the work lies in obtaining regional variations in the assessment of ecological stability of landscapes, which is important to consider when developing coordinated concepts between communities and environmental management bodies on a basin basis to achieve sustainable development goals in socio-ecological systems.
Keywords: river basin; sub-basin; land use; ecosystem services; management decisions; 504.03:911.6+502.57(076)